THE ROLE OF KNOWLEDGE MANAGEMENT IN THE LOCAL SELF-GOVERNMENT SYSTEM - Kozak , O. (Theory and Practice of Public Administration, 2021)
The role of knowledge management  in the local self-government systemDecentralization changes that have taken place in Ukraine over the past five years have changed the paradigm of relations between the citizen and the public, the authorities shifting the emphasis on providing most public services to the basic level - the territorial community. The functions and powers of local self-government bodies have been largely transformed. Various spheres of public and social services to the population and business entities have expanded. Modernization of both political and public management systems in Ukraine provides not only the introduction of new models of personnel management, but also the modernization of these systems using innovative management technologies. One of such management technologies is the management system, which is based on knowledge management.The purpose of this article is to consider approaches to the definition of knowledge management in modern management activities and to justify the need to implement knowledge management in the local government system.The article notes that knowledge, in its broadest sense, is today a highly profitable product. The understanding of the leading role of knowledge in the processes of sustainable development of social systems, the transformation of knowledge into the most important form of capital has been determined. The classification features of knowledge that exist as individual and organizational, autonomous and systemic, external and internal, well-structured and poorly structured (unstructured), explicit and implicit (hidden), positive and negative, are disclosed. The article points out the lack of a clear definition of the concept of knowledge management in the public administration system in the scientific community. This problem negatively affects the efficiency of service delivery processes in the public sector. It also negatively affects the performance of such institutions of public law as local self-government bodies, their ability to ensure the practical use of scientific achievements, organization of interaction and regulation of citizens’ life.The article introduces the author’s approach to the definition of knowledge management in modern management activities. The author presents the differences between the elements of the application of knowledge management in corporate organizations and public authorities. The features of the implementation of the knowledge management system in the activities of local self-government bodies have been determined.The study points out the importance of applying knowledge management in the system of local governments, their role in the changing paradigm of the functioning of the public service.